2023
DOI: 10.21203/rs.3.rs-2608824/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retorting methods of silicon supply on growth stages of spring wheat (Triticum aestivum L.) through skipped irrigation system

Abstract: Plants are exposed to various abiotic stressors in agricultural systems, especially drought stressors, which hinder plant growth and development. Two years field studies have been carried out on two wheat genotypes viz; chakwal-50 (drought tolerant) and sehar-06 (drought sensitive) under skipped irrigation systems via; three methods of silicon (Si) supply along with control treatment at Research Farm Area, Department of Agronomy, University of Agriculture, Faisalabad, Punjab-Pakistan, were focused to optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Irrigation's primary effect can be summarized as follows: I 1 > I 5 > I 6 > I4 > I 3 > I 2. Results table 5 shows straw yields ranged from 7.756 to 9.541 Mgha -1 for plants that did not receive silicates, according to I 1 (withholding irrigation at tillering) and I 0 (without withholding The current findings are consistent with those reported by [13] [1], who indicated that tillering, elongation, booting, and grain production are all moisture-sensitive.…”
Section: -Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Irrigation's primary effect can be summarized as follows: I 1 > I 5 > I 6 > I4 > I 3 > I 2. Results table 5 shows straw yields ranged from 7.756 to 9.541 Mgha -1 for plants that did not receive silicates, according to I 1 (withholding irrigation at tillering) and I 0 (without withholding The current findings are consistent with those reported by [13] [1], who indicated that tillering, elongation, booting, and grain production are all moisture-sensitive.…”
Section: -Results and Discussionsupporting
confidence: 88%
“…One of the most crucial strategies for water conservation in irrigated agriculture is irrigation scheduling. Water resource management to satisfy crop needs can be aided by water management during the growth stages [13].…”
Section: -Introductionmentioning
confidence: 99%